COMPARATIVE STUDY OF TECTONOMAGMATIC EVOLUTION OF THE EARTH AND MOON: KEY FOR UNDERSTANDING THE FORMATION AND INTERNAL EVOLUTION OF SOLID TERRESTRIAL PLANETS - Sharkov E.V.; Bogatikov O.A. (My University, 2003)
Geological and petrological study of the evolution of the Earth and Moon, as well as data on Venus and Mars, showed that all solid terrestrial planets presumably were initially heterogeneous and developed according to a common scenario, which involved gradual heating of their interiors up to the formation of a liquid core and associated gradual cooling of their outer shells. Such a character of heating was supposedly provided by a wave of centripetal deformations, which arise in a rotating body. At the first phase of evolution, tectonomagmatic processes were related to the ascent of superplumes formed in a depleted mantle. The appearance of liquid cores initiated the ascent of geochemically enriched superplumes of the second generation from the core-mantle boundary. They reached moderate depths, and the spread of their heads led to a fundamental reconstruction of planetary surfaces.